Pengaruh Kualitas Produk, Harga dan Label Halal terhadap Niat Beli Ulang dengan Customer Experience sebagai Variabel Mediasi (Studi Pada Remaja Perempuan Pengguna Kosmetik Emina) - Hilmiyatul Makkiyah; Anik Lestari Andjarwati (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
Cosmetics have now become the primary need for women to get their beauty. The development of cosmetics in Indonesia is also increasing. Emina is a local and new cosmetic product with the most users and sells quickly among other local cosmetic products. This study analyses product quality, price, and halal labels on repurchase intentions with customer experience as a mediating variable. This research is aimed at young women who use Emina cosmetics. The sample used was 210 respondents. The sampling method uses a Likert scale. The analysis in this study used Path analysis with Amos software version 24. The results showed that product quality, price and the halal label positively and significantly affected repurchase intention. The results of this study also show that product quality, price and halal label have a direct and significant effect on repurchase intention through customer experience. The mediation test states that customer experience strengthens the influence of product quality, price, and halal label variables on repurchase intentions with the results of a partial mediation role. Local cosmetic brands must continue to improve and develop product quality, especially lip products, and provide reasonable prices, more customer benefits, and halal product labels to maintain favourable customer perceptions and encourage repurchase intentions.